Consistency of Parental and Self-Reported Adolescent Wellbeing: Evidence From Developmental Language Disorder - Gough Kenyon, Sheila M.; Palikara, Olympia; Lucas, Rebecca M. (Frontiers in Psychology, 2021)
Research on adolescent wellbeing in Developmental Language Disorder (DLD) has previously been examined through measures of parent (proxy) or self-reported wellbeing, but never has a study included both and enabled comparison between the two. The current study reports parent and self rated wellbeing of adolescents with DLD and Low Language (LL) ability, as well as their typically developing (TD) peers. It also examines consistency between raters and factors influencing correspondence. Adolescents aged 10-11 with DLD (n = 30), LL (n = 29) or TD (n = 48) were recruited from eight UK primary schools. A battery of standardized language, psychosocial and wellbeing assessments, including the KIDSCREEN-27 (KIDSCREEN Group Europe, 2006) were administered. Adolescent ratings of wellbeing were similar across groups on three of the five wellbeing dimensions, but those with DLD had lower self-reported Autonomy and Parental Relations than their TD peers, and both the DLD and LL group had lower School Environment scores than their TD peers. By parental report, the DLD and LL group were considered to have lower wellbeing on all five wellbeing dimensions relative to their TD peers. Paired sample t-test analyses indicated a high level of variance between parent and adolescent reported wellbeing for multiple wellbeing domains, especially Psychological Wellbeing. Importantly, predictors of the level of agreement between parent and adolescent reported psychological wellbeing differed between groups: cognitive reappraisal and sociability predicted this level of agreement for adolescents with LL while social competence predicted agreement in DLD and TD. This study emphasises the necessity of allowing adolescents of all language abilities to report their own wellbeing, as their perspective does not align with that of their parents. It also highlights the importance of including the full spectrum of need when investigating the impact of language ability on consistency between proxy and self-reported wellbeing.